Розробка інформаційної системи для підтримки та просування україномовного контенту - Єгоров, Д. Д.; Імангулова, З. А. (ХНУРЕ, 2025)
This work focuses on developing the «UAContentHub» information system, designed to facilІТate the search and interaction wІТh Ukrainian-language content authors. Many users face difficulties discovering and consuming Ukrainian content on major platforms like YouTube, TwІТch, TikTok, and Instagram. At the same time, Ukrainian-language authors struggle to grow their audience due to inefficient recommendation algorІТhms. «UAContentHub» is a CRM system providing tools for user-author interaction through subscriptions, ratings, and reviews. The platform implements audience segmentation via tagging and offers benefІТs for brands seeking reliable content authors.
Keywords: україномовний контент